(untitled) (Comprehensive Journal of Science, 2026)
The capacity of each lexical item to relate to the words or structures that precede and follow it constitutes the basis for the sequencing of discourse, which forms the central premise of this study. The full realization of the semantic meaning of any sentence or syntactic construction can only be achieved through attention to the phenomenon of collocation among its components. Meaning is thus shaped by the presence or absence of such syntactic interdependence, and any change in word order is accompanied by a corresponding change in meaning. This paper sheds light on the phenomenon of collocation within the components of syntactic constructions in their various types and forms, examining the arrangement of letters and words within the sentence and the impact of this arrangement on the interpretation of the construction. It further argues that syntactic collocation is fundamentally characterized by connection and cohesion, although this principle may be overridden in accordance with contextual guidance and its requirements